Employers and labour problems. Employers and Trade Unions, by G. Pollock. Automation, by A. Albu. Recent advances in personnel management, by T.G.P. Rogers [...] (London, 1956)
Special number of "The Political Quarterly", vol. 27, 3 (July-Sept. 1956).